2017
DOI: 10.3832/ifor2135-010
|View full text |Cite
|
Sign up to set email alerts
|

Use of overburden waste for London plane (Platanus × acerifolia) growth: the role of plant growth promoting microbial consortia

Abstract: (1)Overburden waste dumps represent a huge threat to environmental quality. The reduction of their negative impact can be achieved by vegetation cover establishment. Usually, this action is complicated due to site-specific characteristics, such as nutrient deficiency, elevated metal concentration, low pH value, lack of moisture and lack of organic matter. Establishment of vegetation can be facilitated by inoculation with plant growth promoting bacteria (PGPB) which improve the physicochemical and biological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In this study, we investigated the possibility of using B. amyloliquefaciens D5 ARV and SMF in priming of old white mustard seed. Karličić et al [2017] had shown that B. amyloliquefaciens D5 ARV used in the current research has the potential for application in sustainable cultivation of plants, aimed to alleviate environmental stress. On the other hand, beneficial effects of SMF on plant growth are well‐documented and Ćirković et al [2017] showed that application of SMF increased germination speed of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the possibility of using B. amyloliquefaciens D5 ARV and SMF in priming of old white mustard seed. Karličić et al [2017] had shown that B. amyloliquefaciens D5 ARV used in the current research has the potential for application in sustainable cultivation of plants, aimed to alleviate environmental stress. On the other hand, beneficial effects of SMF on plant growth are well‐documented and Ćirković et al [2017] showed that application of SMF increased germination speed of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of rhizobacteria to produce phytohormones has long been believed to be a major factor affecting plant root growth; specifically, it is thought that these phytohormones allow the plant to extract nutrients from a greater volume of soil (Egamberdieva et al, 2017). Additionally, other studies have shown that IAA produced by PGPR affects tree root morphology (George et al, 2013) and metabolic processes such as photosynthesis, biosynthesis of various metabolites, and resistance to stressful conditions modulated by auxins (Egamberdieva et al, 2017;Karličić et al, 2017). Accordingly, IAA indirectly increases water and nutrient supplies leading to higher root exudation and biomass production in forest species (Egamberdieva et al, 2017;Karličić et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies have shown that IAA produced by PGPR affects tree root morphology (George et al, 2013) and metabolic processes such as photosynthesis, biosynthesis of various metabolites, and resistance to stressful conditions modulated by auxins (Egamberdieva et al, 2017;Karličić et al, 2017). Accordingly, IAA indirectly increases water and nutrient supplies leading to higher root exudation and biomass production in forest species (Egamberdieva et al, 2017;Karličić et al, 2017). Furthermore, it has been shown that IAA triggers the activation of the central energy metabolism of Escherichia coli cells (Bianco et al, 2006b) and is also able to enhance protection against various abiotic stresses such as UV and low pH (Bianco et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations